ONLINE COMPULSIVE BUYING BEHAVIOR IN GEN Z IN INDONESIA: (Revista Galega de Economía)
This study aims to explore the antecedents of compulsive buying patterns derived from a brand's emotional factors such as credibility, prestige, trust, and brand familiarity. This study also explores other possible roles of brand trust and familiarity that have not been touched upon in previous research. A total of 199 respondents were taken using purposive sampling, testing the relationship between variables using the PLS method. The results showed that compulsive buying patterns are influenced by brand credibility, prestige, trust, and familiarity. Moreover, brand trust and brand familiarity are able to mediate the relationship between brand credibility and prestige towards compulsive buying. The findings of this study can be a contribution for market players to strengthen product credibility and prestige to increase brand trust and familiarity which leads to compulsive purchases of the same brand.